The realistic positioning of UVA1 phototherapy after 25 years of clinical experience and the availability of new biologics and small molecules: a retrospective clinical study - Calzavara-Pinton, Piergiacomo; Bettolini, Luca; Tonon, Francesco; Rossi, Mariateresa; Venturini, Marina (Frontiers in Medicine, 2023)
Background Since the early 1990s, Ultraviolet (UV) A1 phototherapy has been described as an effective and safe treatment of a multitude of skin disorders. However, after 30 years, its use has remained limited to few dermatological centers. Objective To analyze the changes over the years and the current position of UVA1 phototherapy through a Real-World Evidence (RWE) study at a single tertiary referral center. Methods We reviewed the medical files of 740 patients treated between 1998 and 2022. Treatment results were collected, efficacy was assessed by a grading scale and acute adverse effects were registered. Results We treated patients with 26 different diseases. We registered marked improvement (MI) or complete remission (CR) in 42.8% of patients with morphea, 50% with Urticaria Pigmentosa, 40.7% with Granuloma annulare and 85.7% with skin sarcoidosis. Good results were obtained also in the treatment of chronic Graft Versus Host Disease (GVHD), Eosinophilic Fasciitis, Sclero-atrophic Lichen, skin manifestations of systemic lupus erythematosus and psoriasis of HIV+ patients. Systemic Sclerosis, Romberg’s Syndrome, Bushke’s Scleredema, Nephrogenic Fibrosing Dermopathy, REM Syndrome, Follicular Mucinosis, Pretibial Myxedema, Scleromyxedema, pemphigus foliaceus, chronic cutaneous lupus erythematosus, erythroderma of Netherton Syndrome and Necrobiosis Lipoidica were no or poorly responsive. In clinical indications where UVA1 was used as a second line phototherapy after narrow-band (NB)-UVB, we saw good MI or CR rates in Mycosis Fungoides (57% of patients), Atopic Dermatitis (33.9%), Pitiryasis Lichenoides chronica (50%), Pityriasis Lichenoides et varioliformis acute (75%) and Lymphomatod Papulosis (62.5%). Short-term adverse events were uncommon and mild. Conclusion Over the past decade, the annual number of treated patients has progressively declined for several reasons. Firstly, UVA1 phototherapy has taken a backseat to the cheaper and more practical NB-UVB phototherapy, which has proven effective for common indications. Secondly, the emergence of new, safe, and effective drugs for conditions such as atopic dermatitis, GVHD, and connective tissue disorders. Finally, our research has shown that UVA1 therapy is often ineffective or minimally effective for some rare diseases, contrary to previous case reports and small case series. Nonetheless, UVA1 continues to be a valuable treatment option for patients with specific skin disorders.